Mickiewicz. Poeta alternatyw - Dopart, Bogusław (Wydawnictwo Księgarnia Akademicka, 2021)
MICKIEWICZ. A POET OF ALTERNATIVES The title of the present monograph refers to one of the most fundamental traits of the oeuvre and literary life of Adam Mickiewicz. While constantly occupied with invigorating and broadening the subject- -matter of his works, Mickiewicz is careful to follow a steady track of ideas, concepts, and truths. In constructing successive models of poetic worlds and varying them even within single works, he incessantly integrates them into a dynamic, open universe of the ‘man of transformations’ (in Wacław Borowy’s phrasing) in accordance with the ontic position and experience of a Romantic writer. Diversity and variance of poetic forms in Mickiewicz is counterbalanced by his leaning towards regularity and structural connectedness: cycles. As early as his first critical manifesto, he opposes a schematic labeling of his creative output; he presents the history of European poetry in terms of overlapping traditions and gradual differentiation of national literatures.